2020
DOI: 10.1002/adfm.202000543
|View full text |Cite
|
Sign up to set email alerts
|

Bi‐Layered Tubular Microfiber Scaffolds as Functional Templates for Engineering Human Intestinal Smooth Muscle Tissue

Abstract: Designing biomimetic scaffolds with in vivo-like microenvironments using biomaterials is an essential component of successful tissue engineering approaches. The intestinal smooth muscle layers exhibit a complex tubular structure consisting of two concentric muscle layers in which the inner circular layer is orthogonally oriented to the outer longitudinal layer. Here, a 3D bi-layered tubular scaffold is presented based on flexible, mechanically robust, and well aligned silk protein microfibers to mimic the nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 63 publications
0
32
0
Order By: Relevance
“…The manual rolling assembly is mainly developed to produce 3D scaffolds with TMA by warping around a mandrel (Table 3D), such as single-step rolling of stacked two strips with opposing ±30° alignment [78][79][80] or one strip having alternating ±30° patterned regions [102] into an angle-ply multilamellar scaffold for annulus fibrosus, and orthogonal rolling of sheets into bilayered scaffolds for smooth muscle. [13] During this rolling process, the tubular dimensions including outer diameter, inner diameter, and height can be regulated easily by changing the mandrel diameter, the number of wrapped lamellas and the width of 2D aligned building blocks, respectively. Additionally, the rolling assembly also has demonstrated the ability to create directly the columnar scaffolds, [10,65] and transform into nanofibrous bundles [69] or small tubes [66] as 1D aligned building blocks for engineering the HUA without a mandrel (Table 3D).…”
Section: Modular Assembly Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The manual rolling assembly is mainly developed to produce 3D scaffolds with TMA by warping around a mandrel (Table 3D), such as single-step rolling of stacked two strips with opposing ±30° alignment [78][79][80] or one strip having alternating ±30° patterned regions [102] into an angle-ply multilamellar scaffold for annulus fibrosus, and orthogonal rolling of sheets into bilayered scaffolds for smooth muscle. [13] During this rolling process, the tubular dimensions including outer diameter, inner diameter, and height can be regulated easily by changing the mandrel diameter, the number of wrapped lamellas and the width of 2D aligned building blocks, respectively. Additionally, the rolling assembly also has demonstrated the ability to create directly the columnar scaffolds, [10,65] and transform into nanofibrous bundles [69] or small tubes [66] as 1D aligned building blocks for engineering the HUA without a mandrel (Table 3D).…”
Section: Modular Assembly Methodsmentioning
confidence: 99%
“…Providing sufficient mechanical strength for loadbearing function, guiding AF cell oriented growth and ECM deposition, and supporting differentiation of mesenchymal stem cells (MSCs) to chondrogenic lineage [77][78][79][80]93,[96][97]102,172] Smooth muscle in intestines Guiding organization of SMCs similar to that of circular and longitudinal smooth muscle [13,81,82] Blood vessel Recovering the SMCs and ECs into in vivo morphology [83,101,135,193,194] As mentioned above, skeletal muscle is a typical HUA tissue composed of long and thick myofibers that fused and differentiated from myoblasts, thus the scaffolds for skeletal muscle have been developed for mimicking the HUA architecture to present critical topographical cues for prealignment of the myoblasts, guiding the myoblasts fusion, promoting myotube formation and possible maturation into functional myofibers, and maintaining the hierarchical arrangement of myotubes, aiming to regenerate the structure and function of volumetric muscle defects.…”
Section: Annulus Fibrosusmentioning
confidence: 99%
See 1 more Smart Citation
“…Differentiated functional neurons were shown through real time force generation and staining showed innervation of SMCs [ 75 , 130 132 ]. Finally, a 3D bi-layered silk protein scaffold has been utilized as a support ECM for intestinal smooth muscle cells and have been shown to support cell function, differentiation, and neurite growth [ 133 ].…”
Section: Current Approaches To Gi Bioengineeringmentioning
confidence: 99%
“…For example, the 3D geometry of intestinal villi can be printed using an extrusion-based printing system. [93] In addition, a tubular scaffold can provide 3D geometries for cell accommodation [12,14] or a tubular architecture could be spontaneously generated by cellular self-organization after printing. [15] It has been previously reported that such a hollow tubular structure provides distinctive advantages in intestine models: a physiological oxygen gradient can be readily created across the transmural interface, keeping primary epithelial cells viable and properly polarized while providing a platform to coculture anaerobes.…”
Section: Introductionmentioning
confidence: 99%